Pengembangan Sistem Kontrol Lingkungan Mikro Tanaman Aglaonema Berbasis Internet of Things - Wijaya, Alvin Candra; Diena Widyastuti; Didik Suprayitno; Nunuk Hariyani; Sri Sulastri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Aglaonema is an ornamental plant with high aesthetic and economic value, whose growth and quality are strongly influenced by microclimate conditions such as temperature, air humidity, and soil moisture. This study aims to develop an Internet of Things (IoT) based microclimate control system for Aglaonema plants capable of monitoring and controlling environmental conditions automatically and in real time. The system is designed using an ESP32 microcontroller as the main controller, a DHT22 sensor for measuring temperature and air humidity, a soil moisture sensor for monitoring growing media conditions, and actuators consisting of a cooling fan and a water pump. Environmental data are transmitted to the ThingSpeak platform to support remote monitoring. System testing includes sensor accuracy evaluation, actuator response testing, and assessment of the system’s impact on plant growth. The results indicate that the sensors exhibit good accuracy and stability, the actuators operate correctly according to predefined control logic, and the system effectively maintains optimal microclimate conditions for plant growth. The proposed system has the potential to support more efficient and automated Aglaonema cultivation under a limited experimental scale.